Metal oxide-based composite material as well as preparation method and application thereof
By preparing metal oxide-based composite materials, combining ZnO and MnO nanoparticles with a three-dimensional conductive network coated with carbon, the conductivity and cycle stability issues of lithium-ion battery anode materials were solved, achieving high capacity and long lifespan performance at high current densities.
Patent Information
- Application Number
- CN202510970341.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2025-10-31
AI Technical Summary
Existing lithium-ion battery anode materials, such as metal oxides, suffer from low electronic conductivity and volume changes during cycling, leading to reduced battery cycle life. Furthermore, they exhibit low charge/discharge capacity and poor cycle stability at high current densities.
A metal oxide-based composite material, consisting of a matrix and a carbon coating, is used. The matrix is an aggregate of metal oxide nanoparticles with a chemical composition of ZnO·xMnO and a particle size of 200–600 nm. The carbon coating has a mass percentage of 3–10%. The composite material is prepared through hydrothermal reaction and carbonization to construct a three-dimensional conductive network that buffers volume changes.
It improves the charge and discharge capacity and cycle stability of lithium-ion batteries at high current densities, achieving a discharge capacity of 509 mAh/g at high current density and a discharge capacity of 811 mAh/g after 900 cycles at a current density of 1 A/g, suitable for lithium-ion power batteries and energy storage batteries.
Smart Images

Figure CN120878798A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a metal oxide-based composite material, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries are rechargeable batteries that primarily function by the movement of lithium ions between the positive and negative electrodes. Currently, commercially available graphite-based carbon anode materials have a relatively low theoretical specific capacity (372 mAh / g), making it difficult to meet the high energy density requirements of next-generation lithium-ion batteries.
[0003] In comparison, transition metal oxides, such as MnO (theoretical specific capacity of 756 mAh / g), ZnO (theoretical specific capacity of 978 mAh / g), Mn3O4 (theoretical specific capacity of 937 mAh / g), Co3O4 (theoretical specific capacity of 890 mAh / g), Fe2O3 (theoretical specific capacity of 1007 mAh / g), and CuO (theoretical specific capacity of 670 mAh / g), have become a hot research topic in lithium-ion battery anode materials due to their higher theoretical specific capacity. However, the low electronic conductivity of metal oxides and the large volume changes during cycling can easily cause material pulverization, leading to a reduction in battery cycle life.
[0004] Studies have found that composites formed from multiple metal oxides exhibit superior lithium storage performance compared to single oxides due to their synergistic effect. However, the resulting composites still suffer from drawbacks such as low charge-discharge capacity at high current densities and poor cycle stability. Summary of the Invention
[0005] The purpose of this invention is to provide a metal oxide-based composite material, its preparation method, and its application. When the metal oxide-based composite material provided by this invention is applied to the negative electrode of a lithium-ion battery, it can improve the charge-discharge capacity and cycle stability of the lithium-ion battery under high current density.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] This invention provides a metal oxide-based composite material, comprising a matrix and carbon coating located on the surface of the matrix, wherein the matrix is an aggregate composed of metal oxide nanoparticles; the aggregate has an irregular particle shape;
[0008] The particle size of the metal oxide-based composite material is 200–600 nm;
[0009] The chemical composition of the metal oxide nanoparticles is ZnO·xMnO, where x ranges from 0.5 to 2.
[0010] Preferably, the mass percentage of the coated carbon in the metal oxide-based composite material is 3-10%.
[0011] Preferably, the tap density of the metal oxide-based composite material is 1.3–1.7 g / cm³. 3 .
[0012] This invention also provides a method for preparing the metal oxide-based composite material described in the above technical solution, comprising the following steps:
[0013] A water-soluble zinc salt, a water-soluble manganese salt, ethanolamine, and water are mixed to obtain an alkaline mixed salt solution, which is then subjected to a hydrothermal reaction to yield a zinc-manganese precursor.
[0014] The zinc-manganese precursor and an aqueous solution containing an organic carbon source are mixed, and then dried and carbonized sequentially to obtain the metal oxide-based composite material.
[0015] Preferably, the water-soluble zinc salt includes one of zinc nitrate, zinc sulfate, zinc acetate, and zinc chloride;
[0016] The water-soluble manganese salt includes one of manganese nitrate, manganese sulfate, manganese acetate, and manganese chloride.
[0017] Preferably, the molar ratio of the water-soluble zinc salt to the water-soluble manganese salt is 0.5 to 2:1;
[0018] The volume ratio of ethanolamine to water is 1:4 to 8;
[0019] The molar concentration of water-soluble zinc salt in the alkaline mixed salt solution is 0.03–0.18 mol / L.
[0020] Preferably, the temperature of the hydrothermal reaction is 150–170°C, and the holding time is 3–6 hours.
[0021] Preferably, the organic carbon source in the aqueous solution containing the organic carbon source includes at least one of polyacrylic acid, glucono-delta-lactone, sucrose, glucose, and starch;
[0022] The mass concentration of the aqueous solution containing the organic carbon source is 5–15 g / L;
[0023] The mass ratio of the zinc-manganese precursor to the aqueous solution containing an organic carbon source is 1:30 to 80.
[0024] Preferably, the carbonization temperature is 400-600℃, the heating rate to the carbonization temperature is 2-5℃ / min, and the holding time is 2-4h.
[0025] The present invention also provides the application of the metal oxide-based composite material described in the above technical solution or the metal oxide-based composite material prepared by the preparation method described in the above technical solution in the negative electrode of lithium-ion battery.
[0026] This invention provides a metal oxide-based composite material, comprising a matrix and a carbon coating on the surface of the matrix. The matrix is an aggregate composed of metal oxide nanoparticles with an irregular particle shape. The particle size of the metal oxide-based composite material is 200–600 nm. The chemical composition of the metal oxide nanoparticles is ZnO·xMnO, where x ranges from 0.5 to 2. The composite material provided by this invention has a nanoparticle aggregate structure, in which the nanoparticle active material shortens the diffusion path of lithium ions and increases the diffusion rate of lithium ions. The particle size of the composite material is 200–600 nm, exhibiting a non-uniform particle size distribution and an irregular particle shape. This structure facilitates compaction, thereby improving the specific capacity. Simultaneously, the carbon coating in the composite material constructs a three-dimensional conductive network, which not only enhances the conductivity of the composite material but also buffers the volume expansion and contraction during charging and discharging, maintaining the structural integrity of the electrode sheet during long-term cycling. The composite material provided by this invention comprises two metal oxides, ZnO and MnO. Due to the synergistic effect of these two oxides, the electronic / ionic conductivity is improved, resulting in high electrochemical activity and thus enhancing the charge-discharge capacity at high current densities and long-cycle stability. Test results from the embodiments show that the composite material provided by this invention exhibits a discharge capacity as high as 509 mAh / g at a current density of 4 A / g, and retains a discharge capacity of 811 mAh / g after 900 cycles at a current density of 1 A / g, making it suitable as a negative electrode material for lithium-ion power batteries and lithium-ion energy storage batteries.
[0027] This invention also provides a method for preparing the metal oxide-based composite material described in the above technical solution, comprising the following steps: mixing water-soluble zinc salt, water-soluble manganese salt, ethanolamine, and water; subjecting the resulting alkaline mixed salt solution to a hydrothermal reaction to obtain a zinc-manganese precursor; mixing the zinc-manganese precursor with an aqueous solution containing an organic carbon source, and sequentially drying and carbonizing to obtain the metal oxide-based composite material. The preparation method provided by this invention has low-cost reaction raw materials and does not produce harmful substances, making it environmentally friendly; the preparation method includes two steps: hydrothermal reaction and carbonization, with a simple preparation process, strong controllability, and suitability for industrial production, showing good application prospects. Attached Figure Description
[0028] Figure 1 The image shows the XRD pattern of the ZnO·2MnO / C composite material obtained in Example 1.
[0029] Figure 2The image shows a SEM image of the ZnO·2MnO / C composite material obtained in Example 1.
[0030] Figure 3 TEM image of the ZnO·2MnO / C composite material obtained in Example 1;
[0031] Figure 4 The rate performance diagram of the button cell prepared from the ZnO·2MnO / C composite material obtained in Example 1;
[0032] Figure 5 The image shows the long-cycle performance of a button cell prepared from the ZnO·2MnO / C composite material obtained in Example 1.
[0033] Figure 6 The image shows a SEM image of the ZnO·2MnO / C composite electrode sheet obtained in Example 1 after 500 cycles.
[0034] Figure 7 The image shows the XRD pattern of the zinc-manganese precursor obtained in Example 1.
[0035] Figure 8 Here is a SEM image of the zinc-manganese precursor obtained in Example 1;
[0036] Figure 9 The rate performance diagram of the button cell prepared from the zinc-manganese precursor obtained in Example 1;
[0037] Figure 10 The graph shows the long-cycle performance of a button cell prepared from the zinc-manganese precursor obtained in Example 1. Detailed Implementation
[0038] This invention provides a metal oxide-based composite material, comprising a matrix and carbon coating located on the surface of the matrix, wherein the matrix is an aggregate composed of metal oxide nanoparticles; the aggregate has an irregular particle shape;
[0039] The particle size of the metal oxide-based composite material is 200–600 nm;
[0040] The chemical composition of the metal oxide nanoparticles is ZnO·xMnO, where x ranges from 0.5 to 2.
[0041] The metal oxide-based composite material provided by this invention includes a matrix, which is an aggregate composed of metal oxide nanoparticles; the aggregate has an irregular particle shape. In this invention, the chemical composition of the metal oxide nanoparticles is ZnO·xMnO, where x ranges from 0.5 to 2, specifically 0.5, 1.0, 1.5, and 2.0. In this invention, x represents the molar ratio of ZnO to MnO; for example, when x is 0.5, it indicates that the molar ratio of ZnO to MnO is 1:0.5.
[0042] The metal oxide-based composite material provided by this invention includes carbon coating on the surface of the matrix. In this invention, the carbon coating is preferably amorphous carbon. The mass percentage of the carbon coating in the metal oxide-based composite material is preferably 3-10%, specifically 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%. In this invention, the carbon coating in the composite material constructs a three-dimensional conductive network, which not only enhances the conductivity of the composite material but also buffers the volume expansion and contraction during charging and discharging, maintaining the structural integrity of the electrode sheet during long-term cycling.
[0043] In this invention, the particle size of the metal oxide-based composite material is 200–600 nm. In this invention, the tap density of the metal oxide-based composite material is preferably 1.3–1.7 g / cm³. 3 .
[0044] This invention also provides a method for preparing the metal oxide-based composite material described in the above technical solution, comprising the following steps:
[0045] A water-soluble zinc salt, a water-soluble manganese salt, ethanolamine, and water are mixed to obtain an alkaline mixed salt solution, which is then subjected to a hydrothermal reaction to yield a zinc-manganese precursor.
[0046] The zinc-manganese precursor and an aqueous solution containing an organic carbon source are mixed, and then dried and carbonized sequentially to obtain the metal oxide-based composite material.
[0047] This invention involves mixing water-soluble zinc salt, water-soluble manganese salt, ethanolamine, and water to obtain an alkaline mixed salt solution, which is then subjected to a hydrothermal reaction to yield a zinc-manganese precursor.
[0048] In this invention, the water-soluble zinc salt preferably includes one of zinc nitrate, zinc sulfate, zinc acetate, and zinc chloride, with zinc nitrate preferably being zinc nitrate hexahydrate; the water-soluble manganese salt preferably includes one of manganese nitrate, manganese sulfate, manganese acetate, and manganese chloride, with manganese sulfate preferably being manganese sulfate monohydrate. In this invention, the water is preferably deionized water. In this invention, the ethanolamine provides the alkaline environment required for the reaction and also acts as a structure directing agent, resulting in the final zinc-manganese precursor exhibiting a uniform nanoparticle structure.
[0049] In this invention, the molar ratio of the water-soluble zinc salt to the water-soluble manganese salt is preferably 0.5 to 2:1, specifically 0.5:1, 1.0:1, 1.5:1, or 2.0:1; the volume ratio of the ethanolamine to water is preferably 1:4 to 8, specifically 1:4, 1:5, 1:6, 1:7, or 1:8; and the molar concentration of the water-soluble zinc salt in the alkaline mixed salt solution is preferably 0.03 to 0.18 mol / L, specifically 0.03 mol / L, 0.058 mol / L, 0.06 mol / L, 0.09 mol / L, 0.11 mol / L, 0.12 mol / L, 0.16 mol / L, or 0.18 mol / L.
[0050] In this invention, the mixing process is preferably carried out by adding water-soluble zinc salt, water-soluble manganese salt, and ethanolamine to water in sequence and stirring.
[0051] In this invention, the hydrothermal reaction temperature is preferably 150–170°C, specifically 150°C, 160°C, or 170°C; the holding time is preferably 3–6 hours, specifically 3 hours, 4 hours, 5 hours, or 6 hours. In this invention, the hydrothermal reaction is preferably carried out in a hydrothermal reactor lined with polytetrafluoroethylene. In this invention, after the hydrothermal reaction, it is also preferable to allow the obtained system to cool naturally to room temperature, collect the precipitate by filtration, and then sequentially wash and dry the precipitate; the number of water washes is preferably 3; and the drying temperature is preferably 80°C. In this invention, the particle size of the zinc-manganese precursor is preferably 50–100 nm.
[0052] After obtaining the zinc-manganese precursor, the present invention mixes the zinc-manganese precursor with an aqueous solution containing an organic carbon source, and then performs drying and carbonization sequentially to obtain the metal oxide-based composite material.
[0053] In this invention, the organic carbon source in the aqueous solution containing the organic carbon source preferably includes at least one selected from polyacrylic acid, glucono-delta-lactone, sucrose, glucose, and starch; the water in the aqueous solution containing the organic carbon source is preferably deionized water. In this invention, the aqueous solution containing the organic carbon source is preferably obtained by dissolving the organic carbon source in water. In this invention, the mass concentration of the aqueous solution containing the organic carbon source is preferably 5–15 g / L, specifically 5 g / L, 10 g / L, or 15 g / L; the mass ratio of the zinc-manganese precursor to the aqueous solution containing the organic carbon source is preferably 1:30–80, specifically 1:30, 1:40, 1:50, 1:60, 1:70, or 1:80.
[0054] In this invention, the drying method is preferably to stir under heating conditions until the moisture is completely evaporated. In this invention, the heating temperature is preferably 80°C.
[0055] In this invention, the carbonization temperature is preferably 400–600°C, specifically 400°C, 450°C, 500°C, 550°C, or 600°C; the heating rate to the carbonization temperature is preferably 2–5°C / min, specifically 2°C / min, 3°C / min, 4°C / min, or 5°C / min; and the holding time is preferably 2–4 hours, specifically 2 hours, 3 hours, or 4 hours. In this invention, the carbonization is preferably carried out in a protective atmosphere, preferably argon. In this invention, the carbonization is preferably carried out in a tube furnace.
[0056] The present invention also provides the application of the metal oxide-based composite material described in the above technical solution or the metal oxide-based composite material prepared by the preparation method described in the above technical solution in the negative electrode of lithium-ion battery.
[0057] Unless otherwise specified, the materials and equipment used in this invention are all commercially available products in the field.
[0058] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0059] Example 1
[0060] Add 2 mmol zinc nitrate hexahydrate, 4 mmol manganese sulfate monohydrate and 5 mL ethanolamine to 30 mL deionized water in sequence, stir to dissolve and form a homogeneous solution.
[0061] The solution was then transferred to a reaction vessel lined with polytetrafluoroethylene and heated to 170°C for hydrothermal reaction, and kept at that temperature for 5 hours. After the reaction vessel cooled to room temperature naturally, the precipitate was collected by filtration. The precipitate was washed three times with deionized water and dried at 80°C to obtain zinc-manganese precursor (particle size 50-100 nm).
[0062] 0.21 g of polyacrylic acid was dissolved in 30 mL of deionized water, and then 0.49 g of zinc-manganese precursor was added. After continuous stirring at 80 °C to evaporate the water, a solid powder was obtained. The solid powder was placed in a tube furnace and heated to 500 °C at a heating rate of 2 °C / min for 2 h to obtain a ZnO·2MnO / C composite material (where the mass percentage of coated carbon in the composite material is 4.9%, the particle size of the composite material is 200–600 nm, and the tap density is 1.42 g / cm³). 3 ).
[0063] Example 2
[0064] Add 2 mmol zinc nitrate hexahydrate, 2 mmol manganese sulfate monohydrate and 5 mL ethanolamine to 30 mL deionized water in sequence, stir to dissolve and form a homogeneous solution.
[0065] The solution was then transferred to a reaction vessel lined with polytetrafluoroethylene and heated to 170°C for hydrothermal reaction, and kept at that temperature for 5 hours. After the reaction vessel cooled to room temperature naturally, the precipitate was collected by filtration. The precipitate was washed three times with deionized water and dried at 80°C to obtain zinc-manganese precursor (particle size 50-100 nm).
[0066] 0.20 g of polyacrylic acid was dissolved in 30 mL of deionized water, and then 0.49 g of zinc-manganese precursor was added. After continuous stirring at 80 °C to evaporate the water, a solid powder was obtained. The solid powder was placed in a tube furnace and heated to 500 °C at a heating rate of 2 °C / min for 2 h to obtain a ZnO·MnO / C composite material (where the mass percentage of coated carbon in the composite material is 4.6%, the particle size of the composite material is 200–600 nm, and the tap density is 1.44 g / cm³). 3 ).
[0067] Example 3
[0068] Add 2 mmol zinc nitrate hexahydrate, 1 mmol manganese sulfate monohydrate and 5 mL ethanolamine to 30 mL deionized water in sequence, stir to dissolve and form a homogeneous solution.
[0069] The solution was then transferred to a reaction vessel lined with polytetrafluoroethylene and heated to 170°C for hydrothermal reaction, and kept at that temperature for 5 hours. After the reaction vessel cooled to room temperature naturally, the precipitate was collected by filtration. The precipitate was washed three times with deionized water and dried at 80°C to obtain zinc-manganese precursor (particle size 50-100 nm).
[0070] 0.18 g of polyacrylic acid was dissolved in 30 mL of deionized water, and then 0.50 g of zinc-manganese precursor was added. After continuous stirring at 80 °C to evaporate the water, a solid powder was obtained. The solid powder was placed in a tube furnace and heated to 500 °C at a heating rate of 2 °C / min for 2 h under an argon atmosphere to obtain a 2ZnO·MnO / C composite material (where the mass percentage of coated carbon in the composite material is 4.3%, the particle size of the composite material is 200–600 nm, and the tap density is 1.49 g / cm³). 3 ).
[0071] Comparative Example 1
[0072] Add 5 mmol zinc nitrate hexahydrate, 0.625 mmol manganese sulfate monohydrate and 5 mL ethanolamine to 30 mL of deionized water in sequence, and stir to dissolve and form a homogeneous solution.
[0073] The solution was then transferred to a reaction vessel lined with polytetrafluoroethylene and heated to 170°C for hydrothermal reaction, and kept at that temperature for 5 hours. After the reaction vessel cooled to room temperature naturally, the precipitate was collected by filtration. The precipitate was washed three times with deionized water and dried at 80°C to obtain zinc-manganese precursor (particle size 50-100 nm).
[0074] The composite material was prepared according to the method in Example 1, and is designated as 8ZnO·MnO / C composite material (wherein the mass percentage of coated carbon in the composite material is 4.5%, the particle size of the composite material is 200-600 nm, and the tap density is 1.48 g / cm³). 3 ).
[0075] Performance testing
[0076] Test Example 1
[0077] Figure 1 The image shows the XRD pattern of the ZnO·2MnO / C composite material obtained in Example 1. Figure 1 It can be seen that the composite material obtained in this embodiment contains two phases, ZnO and MnO. The sharp diffraction peaks indicate that the material has high crystallinity. Elemental analysis shows that the molar ratio of Zn to Mn is 1:2.05. Therefore, the molar ratio of ZnO to MnO in the composite material is approximately 1:2.
[0078] Figure 7 The image shows the XRD pattern of the zinc-manganese precursor obtained in Example 1. Figure 7 It can be seen that the zinc-manganese precursor obtained by the hydrothermal reaction is a pure-phase ZnMn2O4 material.
[0079] Test Example 2
[0080] Figure 2 This is a scanning electron microscope image of the ZnO·2MnO / C composite material obtained in Example 1. From... Figure 2 It can be seen that the composite material obtained in this embodiment is a nanoparticle aggregate with an aggregate size of 100-400 nm.
[0081] Figure 8 This is a SEM image of the zinc-manganese precursor obtained in Example 1. From... Figure 8 It can be seen that the ZnMn2O4 precursor obtained by hydrothermal reaction is a spherical nanoparticle with a particle size of 50-100 nm, which has good dispersibility.
[0082] Test Example 3
[0083] Figure 3 This is a transmission electron microscope image of the ZnO·2MnO / C composite material obtained in Example 1. From... Figure 3 As can be seen, the composite material obtained in this embodiment is a nanoparticle aggregate with a conductive carbon layer coated on the particle surface.
[0084] Test Example 4
[0085] The composite materials and zinc-manganese precursors obtained in the examples and comparative examples were used as active materials to prepare button batteries, and their electrochemical performance was tested.
[0086] The test method is as follows: Active material, SuperP conductive carbon, and polyvinylidene fluoride binder are mixed in a mass ratio of 75:15:10. An appropriate amount of N-methylpyrrolidone solvent is added and stirred until homogeneous to obtain a slurry. This slurry is then coated onto copper foil and vacuum dried at 70°C to obtain the negative electrode sheet (the loading of active material on the negative electrode sheet is 1.0 mg / cm³). 2 A CR2016 button cell was assembled using a lithium sheet as the counter electrode, a polypropylene porous membrane as the separator, and a solution obtained by dissolving 1 mol of lithium hexafluorophosphate in a mixed solvent of 1 L of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate (volume ratio 1:1:1) as the electrolyte.
[0087] Constant current charge-discharge tests were performed on the CT2001A battery testing system, with a voltage range of 0.01 to 3V.
[0088] Figure 4 The rate performance graph shows the coin cell fabricated from the ZnO·2MnO / C composite material obtained in Example 1. (From...) Figure 4It can be seen that the average discharge capacity is as high as 891 mAh / g at a current density of 0.1 A / g, 820 mAh / g at a current density of 0.2 A / g, 742 mAh / g at a current density of 0.5 A / g, 676 mAh / g at a current density of 1 A / g, 598 mAh / g at a current density of 2 A / g, and still has an average discharge capacity of 509 mAh / g at a high current density of 4 A / g, demonstrating excellent high-rate performance.
[0089] The average discharge capacities of the ZnO·MnO / C composite material obtained in Example 2 at current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, 1 A / g, 2 A / g, and 4 A / g were 880 mAh / g, 809 mAh / g, 732 mAh / g, 663 mAh / g, 582 mAh / g, and 495 mAh / g, respectively.
[0090] The average discharge capacities of the 2ZnO·MnO / C composite material obtained in Example 3 at current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, 1 A / g, 2 A / g, and 4 A / g were 884 mAh / g, 816 mAh / g, 736 mAh / g, 671 mAh / g, 588 mAh / g, and 502 mAh / g, respectively.
[0091] The average discharge capacities of the 8ZnO·MnO / C composite material obtained in Comparative Example 1 at current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, 1 A / g, 2 A / g, and 4 A / g were 782 mAh / g, 656 mAh / g, 585 mAh / g, 530 mAh / g, 428 mAh / g, and 332 mAh / g, respectively.
[0092] Figure 5 The image shows the long-cycle performance of the coin cell prepared from the ZnO·2MnO / C composite material obtained in Example 1. The cell was first activated by cycling three times at a low current density of 0.1 A / g. From... Figure 5 It can be seen that after 900 cycles at a high current density of 1A / g, the discharge capacity is still 812mAh / g, with a capacity retention rate of 112%; indicating that the composite material provided by the present invention can improve the cycle stability of lithium-ion batteries.
[0093] The ZnO·MnO / C composite material obtained in Example 2 retained a discharge capacity of 787 mAh / g after 900 cycles at a high current density of 1 A / g, with a capacity retention rate of 92%.
[0094] The 2ZnO·MnO / C composite material obtained in Example 3 retained a discharge capacity of 798 mAh / g after 900 cycles at a high current density of 1 A / g, with a capacity retention rate of 98%.
[0095] The 8ZnO·MnO / C composite material obtained in Comparative Example 1 retained a discharge capacity of 382 mAh / g after 900 cycles at a high current density of 1 A / g, with a capacity retention rate of 72%.
[0096] Figure 6 This is a scanning electron microscope image of the ZnO·2MnO / C composite electrode sheet obtained in Example 1 after 500 cycles. From... Figure 6 It can be seen that after 500 repeated charge-discharge cycles, there was no obvious cracking of the electrode sheet or shedding of the electrode material, indicating that the electrode sheet can maintain good structural integrity during long cycles, thus giving it a long cycle life.
[0097] Figure 9 The rate performance graph shows that of a button cell prepared from the zinc-manganese precursor obtained in Example 1. Figure 9 It can be seen that the average discharge capacities of ZnMn2O4 materials at current densities of 0.1 A / g, 0.2 A / g, 0.5 A / g, 1 A / g, 2 A / g, and 4 A / g are 841 mAh / g, 699 mAh / g, 606 mAh / g, 526 mAh / g, 445 mAh / g, and 357 mAh / g, respectively. It is evident that the discharge capacity of the uncoated metal oxide material at all current densities is lower than that of the carbon-coated metal oxide material, indicating that carbon coating can significantly improve the rate performance of metal oxide materials.
[0098] Figure 10 The graph shows the long-cycle performance of a button cell prepared from the zinc-manganese precursor obtained in Example 1. Figure 10 It can be seen that after 900 cycles at a high current density of 1 A / g, the ZnMn2O4 material retains only 543 mAh / g of discharge capacity, with a capacity retention rate of 77%. Both the discharge capacity and capacity retention rate after cycling are lower than those of carbon-coated metal oxide materials, indicating that carbon coating can significantly improve the cycling stability of metal oxide materials.
[0099] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A metal oxide-based composite material, characterized in that, It includes a matrix and a carbon coating on the surface of the matrix, wherein the matrix is an aggregate composed of metal oxide nanoparticles; the aggregate has an irregular particle shape; The particle size of the metal oxide-based composite material is 200–600 nm; The chemical composition of the metal oxide nanoparticles is ZnO·xMnO, where x ranges from 0.5 to 2.
2. The metal oxide-based composite material according to claim 1, characterized in that, The coated carbon has a mass percentage of 3-10% in the metal oxide-based composite material.
3. The metal oxide-based composite material according to claim 1 or 2, characterized in that, The tap density of the metal oxide-based composite material is 1.3–1.7 g / cm³. 3 .
4. The method for preparing the metal oxide-based composite material according to any one of claims 1 to 3, characterized in that, Includes the following steps: A water-soluble zinc salt, a water-soluble manganese salt, ethanolamine, and water are mixed to obtain an alkaline mixed salt solution, which is then subjected to a hydrothermal reaction to yield a zinc-manganese precursor. The zinc-manganese precursor and an aqueous solution containing an organic carbon source are mixed, and then dried and carbonized sequentially to obtain the metal oxide-based composite material.
5. The preparation method according to claim 4, characterized in that, The water-soluble zinc salt includes one of zinc nitrate, zinc sulfate, zinc acetate, and zinc chloride; The water-soluble manganese salt includes one of manganese nitrate, manganese sulfate, manganese acetate, and manganese chloride.
6. The preparation method according to claim 4 or 5, characterized in that, The molar ratio of the water-soluble zinc salt to the water-soluble manganese salt is 0.5 to 2:1; The volume ratio of ethanolamine to water is 1:4 to 8; The molar concentration of water-soluble zinc salt in the alkaline mixed salt solution is 0.03–0.18 mol / L.
7. The preparation method according to claim 6, characterized in that, The hydrothermal reaction is carried out at a temperature of 150–170°C for 3–6 hours.
8. The preparation method according to claim 4, characterized in that, The organic carbon source includes at least one of polyacrylic acid, gluconolactone, sucrose, glucose, and starch; The mass concentration of the aqueous solution containing the organic carbon source is 5–15 g / L; The mass ratio of the zinc-manganese precursor to the aqueous solution containing an organic carbon source is 1:30 to 80.
9. The preparation method according to claim 4 or 8, characterized in that, The carbonization temperature is 400–600°C, the heating rate to the carbonization temperature is 2–5°C / min, and the holding time is 2–4 hours.
10. The application of the metal oxide-based composite material according to any one of claims 1 to 3 or the metal oxide-based composite material prepared by the preparation method according to any one of claims 4 to 9 in the negative electrode of a lithium-ion battery.